ERGONOMIC ANALYSIS IN A CONSTRUCTION SITE (Fiep Bulletin - online, 2012)
construction. Thus, this research presents an ergonomic analysis in certain jobs within the construction site of a large building in the city of Curitiba to see what the actual working situation of those who work in such. To achieve this, it was necessary to use as a research tool questionnaire to identify biomechanical problems and measuring equipment (sound level meter, anemometer, thermometer and light meter) to evaluate the environmental factors (noise, ventilation, temperature and brightness) of the 03 jobs analyzed. We analyzed the jobs of circular saw operators, marble saw and cement mixer. The results showed the presence of biomechanics at construction sites, predominantly static that can generate faster fatigue as far as the environmental factors are concerned, which has problems of noise levels, brightness, temperature and ventilation at the sites. Thus, it can be concluded that the building site analysis requires a comprehensive ergonomic study to match the existing ergonomic standards, both with regard to biomechanical problems like the environment, which appeared outside the tolerance limits.
Keywords: Biomechanics; Ergonomic Analysis; Health; Construction.